2020
DOI: 10.3399/bjgpopen20x101053
|View full text |Cite
|
Sign up to set email alerts
|

Referral rates for children with acute gastroenteritis: a retrospective cohort study

Abstract: BackgroundHospital admission rates are increasing for children with acute gastroenteritis. However, it is unknown whether this increase is accompanied by an increase in referral rates from GPs due to increased workloads in primary care out-of-hours (OOH) services.AimTo assess trends in referral rates from primary care OOH services to specialist emergency care for children presenting with acute gastroenteritis.Design & settingThis retrospective cohort study covered a period from September 2007–September 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Paediatrician referrals were made for 19% of children in the present study, far higher than the previously reported rate of 8%, 26 but these almost certainly resulted from the deliberate inclusion of children at increased risk of dehydration; supporting this, the degree of dehydration is known to be among the main reasons for referral and hospitalisation. 27 …”
Section: Discussioncontrasting
confidence: 45%
“…Paediatrician referrals were made for 19% of children in the present study, far higher than the previously reported rate of 8%, 26 but these almost certainly resulted from the deliberate inclusion of children at increased risk of dehydration; supporting this, the degree of dehydration is known to be among the main reasons for referral and hospitalisation. 27 …”
Section: Discussioncontrasting
confidence: 45%
“…In the Askøy outbreak, one infant died with C. jejuni -gastroenteritis as a contributing cause of death. Young children are often brought to OOH services with gastroenteritis [ 21 ], and our findings reveal a significant rise in primary care contacts for young children during this outbreak, particularly in those under five years old.…”
Section: Discussionmentioning
confidence: 84%
“…Overall, ORT intake was low (10 ml/4 hours) and referral rates were high (19% in comparison with a mean referral rate of 8.1%). 3 Ondansetron use did not appear to increase ORT intake or lead to fewer hospital referrals or admissions; nevertheless, parents were more satisfied with the addition of ondansetron compared with ORT alone.…”
Section: Discussionmentioning
confidence: 86%
“…About 5% of all general practitioner (GP) consultations with children in the Netherlands are for AGE (2). Among those seen in primary care, 8.1% are referred to specialist care and 8000 are admitted to the hospital each year (2,3). However, it is thought that many of these referrals and admissions can be avoided (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation